Integrated transportation and land use regression modelling for nitrogen dioxide mitigation - O'Mahony, Margaret; Broderick, Brian (My University, 2023)
The transport sector has been identified as one of the main contributors to nitrogen dioxide (NO2) pollution in Ireland. This research develops an enhanced Wind Sector Land Use Regression (WS-LUR) model to estimate NO2 concentrations across Ireland, in areas where air pollution monitoring is not available. The model incorporates details of the vehicle fleet breakdown to weight vehicle type flows based on the emission rates of the vehicle type, differentiating routes with varying proportions of heavier emitting vehicles. In 2008, car taxation underwent a significant change from an engine size based system to a carbon dioxide (CO2) emission rate based system resulting in a significant transition towards diesel fuelled vehicles. A mitigation strategy to remove diesel fuelled vehicles from the public service vehicle fleet was tested achieving predicted NO2 reductions in the range of 0.3 μg/m3 to 1.9 μg/m3. The impact of COVID-19 on NO2 concentration levels was also investigated.
PUBLISHED
Keywords: Land use regression; Nitrogen dioxide (NO2); Vehicle type; Mitigation; Smart & Sustainable Planet; Air Pollution; Environmental aspects of transportation; Environmental engineering; Land Use Planning/Policy; NO2; NO2 mitigation; Simulation and modelling transportation networks; Transportation Engineering; nitrogen dioxide